Surface-Modified Dielectric Materials for Transistor - Ha, Young-Geun; Lee, Sunyoung; Park, Jong-Ho; Lee, Chi-Gyu; Song, Kyuseok (Asian Journal of Chemistry, 2013)
Organic field-effect transistors operating at low voltage (< 2 V) have been fabricated using new solution-processable nanoscale dielectric as the gate dielectric material. In this paper, we demonstrate that a monolayer of octadecyltrichlorosilane on top of nanoscale dielectric shows good improved dielectric properties with optimized changing the surface characteristics and good insulating property with leakage current densities as low as 10-7 A/cm2 at 1 V and capacitance value approaching 420 nF/cm2. The corresponding pentacene transistors based on these dielectrics exhibit improved performance with hole mobility of ~ 0.2 cm2/Vs and Ion/Ioff ratio ~ 105.